External operating environment and resiliency of foreign ethnic restaurant / Mohd Noor Azmin Akbarruddini...[et al.] - Mohd Zahari, Mohd Salehuddin; Suhaimi, Mohd Zulhilmi (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2017)
The presence of foreign ethnic restaurants has become a norm in this country. The establishment of such restaurant has been increasing steadily especially in the recent decades. This phenomenon is certainly could be attributed to some elements that motivate foreigners to open their businesses in this country. This study aims to uncover the underlying reasons for the foreigners to open their restaurants and how the external operating environment affect their restaurant businesses’ resiliency. Furthermore, there has been a lack of study looking into external operating environment and resiliency of a business. Therefore, this warrant an investigation on the issue at hand.